ANALISIS PERANAN GURU KELAS DALAM MENGELOLA PEMBELAJARAN MELALUI KURIKULUM 2013 SISWA KELAS V SDN 17 MUNGGUK KECAMATAN SEKADAU HILIR TAHUN PELAJARAN 2020/2021 - Agusta Kurniati; Muhammad Rian Subekti; Meri Okta Vera (STKIP Persada Khatulistiwa Sintang, 2021)
The purpose of this research was to know the role of clasroom teacher in educational management through curriculum of 2013 at student class V SDN Mungguk Kecqamatan Sekadau Hilir. This research was used descriptive qualitative method and the form of descriptive qualitative research. The tools were used observation sheet, interview, and documentation. The results show that in the learning process the teacher is not only teaching and delivering material but the teacher must also be able to solve psychological things that may be present and experienced by their students, therefore the teacher can act as a motivator, facilitator, organizer, informant, and corrector. There were supporting and inhibiting factors experienced by teachers in Educational management through curriculum of 2013, the supporting factor was that the principal always sends teachers to always participate in KKG activities, while the inhibiting factor was in the delivery of material, giving assessments, and utilizing existing media sources because the teacher at SDN 17 Mungguk the majority were senior teachers. The efforts made by the teacher to overcome these factors were that the teacher must understand the character of each student, approach students, the teacher must not assume the abilities of all students were the same because basically every child has different characters and abilities and the teacher always provides motivation and enthusiasm. so that students continue to learn.